2008
DOI: 10.2310/7290.2008.00024
|View full text |Cite
|
Sign up to set email alerts
|

Stably Integrated luxCDABE for Assessment of Salmonella Invasion Kinetics

Abstract: Salmonella Typhimurium is a common cause of gastroenteritis in humans and also localizes to neoplastic tumors in animals. Invasion of specific eukaryotic cells is a key mechanism of Salmonella interactions with host tissues. Early stages of gastrointestinal cell invasion are mediated by a Salmonella type III secretion system, powered by the adenosine triphosphatase invC. The aim of this work was to characterize the invC dependence of invasion kinetics into disparate eukaryotic cells traditionally used as model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Consistent with previous studies, 26,56,[64][65][66][67] we observed that an InvC deficiency caused a significant impairment of bacterial entrance to non-phagocytic cells, as compared with WT Salmonella. Lack of InvC is thought to render Salmonella unable to translocate the SPI-1-derived effector molecules required to induce phagocytosis by epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, 26,56,[64][65][66][67] we observed that an InvC deficiency caused a significant impairment of bacterial entrance to non-phagocytic cells, as compared with WT Salmonella. Lack of InvC is thought to render Salmonella unable to translocate the SPI-1-derived effector molecules required to induce phagocytosis by epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…The second strategy involves the use of the entire lux operon from a bacterium such as Photorhabdus luminescens (formerly Xenorhabdus luminescens ). A transposon insertion or plasmid vector containing the luciferase enzyme, as well as the components for substrate production can be engineered with a transposon insertion (Flentie et al, 2008). This system will emit light in the range of 495–500 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of PhoP-PhoQ two-component system has always been linked to major intramacrophage survival defects and marked attenuation in the murine typhoid model. Hence, human cancer cell lines are commonly used to study invasion of Salmonella to eukaryotic cells [19]. The attenuated Salmonella used in this study still maintained its ability to invade MCF-7 and MCF-10A mammalian cells, where 1.2% and 0.5% of the cells were infected, respectively.…”
Section: Discussionmentioning
confidence: 87%